Pelatihan Software Akuntansi untuk Musyawarah Guru Mata Pelajaran Ekonomi Daerah Istimewa Yogyakarta - Kurniawati, Anggreni Dian; Widyatini, Ignatia Ryana; Setiawan, Wimpie Yustino; Pratama, Yohanes Mario; Iswari, Tabita Indah; Budiharta, Pratiwi; Budisantoso, Totok; Purwaningsih, Anna (Jurnal Atma Inovasia, 2024)
Economic disruption and changes in corporate operations in the Fourth Industrial Revolution will necessitate the understanding and control of artificial intelligence, or robots. This is a major issue, but it is also important for economic teachers to introduce companies that are already successful and sophisticated. Accounting software may help make bookkeeping, analyzing, reporting, and investigating easier and more precise; this concludes an opportunity in this era. Therefore, educational institutions must develop graduates who are adaptable and have soft skills. The Accounting Program and Financial Accounting Pillar team respond to economic teachers at MGMP in the Special Region of Yogyakarta by organizing a discussion forum and simulation to provide them with knowledge and best practices for using accounting software to manage business activities and achieve effective and efficient business outcomes. These exercises involve a class lecture using an andragogic approach. The discussion results suggest that economic teachers have best practices to offer accounting software to their pupils. On the other hand, it can increase teaching motivation for improving both financial and technology for themselves and the topic itself.